2006
DOI: 10.1099/ijs.0.02917-0
|View full text |Cite
|
Sign up to set email alerts
|

RFLP analysis of the rRNA operon of a Brazilian collection of bradyrhizobial strains from 33 legume species

Abstract: Genetic diversity in tropical rhizobial species is still poorly known. With the aim of increasing this knowledge, three ribosomal regions of 119 strains belonging to the official Brazilian culture collection of rhizobia and classified as Bradyrhizobium based on morphological and physiological characteristics in vitro were analysed by RFLP-PCR. The strains were isolated from 33 legume species, representing nine tribes and all three subfamilies; they all form very effective N 2 -fixing nodules and 43 of them are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
1
27

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 52 publications
(110 reference statements)
6
41
1
27
Order By: Relevance
“…Gels were stained with ethidium bromide, visualized under UV radiation, and photographed. As in previous studies by our group (Germano et al 2006), the profiles obtained were confirmed in triplicate.…”
Section: Rhizobial Isolationsupporting
confidence: 72%
“…Gels were stained with ethidium bromide, visualized under UV radiation, and photographed. As in previous studies by our group (Germano et al 2006), the profiles obtained were confirmed in triplicate.…”
Section: Rhizobial Isolationsupporting
confidence: 72%
“…Although many members of mimoseae have been studied for rhizobial symbionts, [15][16][17] this legume, in spite of its availability in the tropics, is unreported in this regard. In the present study, polyphasic analysis, including phenotypic and molecular taxonomic approaches, revealed that the isolated strain represents a novel species of the genus Bradyrhizobium, for which we propose the name Bradyrhizobium iriomotense sp.…”
mentioning
confidence: 99%
“…(EARDLY, et al, 2005;RASHID et al, 2009). Pela análise do perfil de restrição individual com cada enzima de restrição, existe um indicativo de que o maior poder discriminatório poderia ser atribuído à Dde I. Contudo, conforme também salientado em outros estudos (GERMANO et al, 2006), o posicionamento taxonômico correto só é possível com a análise de várias enzimas de restrição. Recomenda-se, portanto, o uso de mais de uma endonuclease de restrição para a caracterização das estirpes de rizóbios.…”
Section: Resultsunclassified
“…Dados de sequências da região espaçadora entre os genes 16S-23S rDNA têm se acumulado nos últimos anos, e o alinhamento de sequências disponíveis em bancos de dados mostra que pode ocorrer variação considerável intra e infra-específica, tanto no tamanho como na sequência de bases (LAGUERRE, et al, 1996;CHUEIRE, et al, 2003;GERMANO, et al, 2006), evidenciando que esta região pode ser útil na diferenciação de estirpes de rizóbios recomendadas para produção de inoculantes.…”
Section: Introductionunclassified